Analysis of Taklinear Performance and Integer Linear Programming Models in Nurses Scheduling Problems - Nababan, Junerdi; Tulus, Tulus; Situmorang, Zakarias (Politeknik Ganesha Medan, 2020)
Almost all hospitals schedule nurses' work shifts manually, which is not effective, mistakes in scheduling nurses in hospitals can make them not work optimally so that they are prone to making mistakes and will endanger every patient in the hospital. In the research will be proposed integer linear programming model and branch and bound method, the purpose of this study is to develop an optimization model of nurse scheduling problems at the hospital. The optimization model will minimize the total deviation of nurses' working days from the standard workdays, the optimization model implemented in hospitals is processed using LINGO software.